The effect of information technology on competitive advantage of firm: The role of environmental uncertainty - Berrich Abdelkader; Benkaddour Abed (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
The aim of this study is to assess the relationship between IT and the competitive advantage of firms. Beside the adoption of Resource-Based View (RBV) as a theoretical framework, this work tries to find out the moderation effect of environmental uncertainty, as a contextual variable in the relationship between IT and competitive advantage of firm. Using data from 36 Algerian firms and multiple regression analysis with Process Macro, the regression analysis show no moderation effect of environmental uncertainty in the relationship between IT and competitive advantage (even the model is statistically significant), probably due to the small sample size adopted. Finally, this work drives its importance from the multiple dimensions adopted in measuring IT from IS literature, which is compatible with the complementarity of resources that leads to competitive advantage of firms according to Resource-Based View. Moreover, even the small dataset used in this study, this last contribute to the field of research when it try to explain competitive advantage of the firm from inside (resources) and outside (environment) perspectives.
Keywords: 650; Information technology; IT infrastructure; IT technical skills; IT business partnership; competitive advantage; environmental uncertainty